The Effect of Development and Financial Performance of Sharia Bank on Service Quality and Customer Satisfaction - Zen, Agustian; Nazira, Nafwa Ayu; Willson, Michael Aris; Salsabila Aninda Putri; Pangeswati, Saron Okavia (AFEBI Islamic Finance and Economic Review, 2023)
This study aims to determine the effect of development and financial performance of Islamic banks on service quality and customer satisfaction in Indonesia. The method used is inductive qualitative. This approach uses a qualitative approach that focuses on library research. Sources of data come from references from books, journ als, and related research. Data collection techniques use literature studies, expert books, and relevant scientific journals. Data analysis was carried out by searching, collecting and qualitatively comparing the various insights obtained. The research findings are carried out comprehensively and are related to various concepts and relevant literature studies. The results showed that the development of Islamic banks has a positive effect on service quality, financial performance has a positive effect on service quality, development of Islamic banks has a positive effect on customer satisfaction, financial performance has a positive effect on customer satisfaction, and service quality has a positive effect on customer satisfaction. The conclusion obtained is that the development of Islamic banks has a positive effect on service quality and customer satisfaction, financial performance has a positive effect on service quality and customer satisfaction, and service quality has a positive effect on customer satisfaction.